Pemberdayaan Ekonomi Lokal Melalui Pengembangan Wisata Kuliner Mbalong Kawuk Desa Sumberejo Kulon - Riana, Cahaya; Rizqiana, Isyarotur; Syilviana, Renita; Nur Aisyah, Sindy; Ti’anatud Diniati, Bintis (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of Mbalong Kawuk culinary tourism development in empowering the local economy of the Sumberejo Kulon Village community, Ngunut District, Tulungagung District. Using a descriptive qualitative method with a case study approach, data was obtained through observation, interviews, and documentation. The results showed that the development of this culinary tourism area succeeded in increasing some of the income of the Sumberejo Kulon Village community, creating new business opportunities, and strengthening local cultural identity through culinary preservation. The village government and BUMDes Sumber Mulyo have an active role in managing the tourism area based on community participation. In addition to providing economic impact, this development also strengthens social relations and builds a sense of belonging to tourist destinations. This study concludes that local-based empowerment and community participation are effective in driving sustainable village economic growth, and this representation can be replicated in other areas.